2020
DOI: 10.1101/2020.07.17.20155960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Observational Study of the Efficiency of Treatments in Patients Hospitalized with Covid-19 in Madrid

Abstract: Background Many different treatments were heavily administered to patients with COVID-19 during the peak of the pandemic in Madrid without robust evidence supporting them. Methods We examined the association between sixteen treatments in four groups (steroids, antivirals, antibiotics and immunomodulators) and intubation or death. Data were obtained from patients that were admitted to an HM hospital with suspicion of COVID-19 until 24/04/2020, excluding unconfirmed diagnosis, those who were admitted before the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…In this paper, we analyze the anonymized dataset obtained from the HMhospitals’ network in Madrid (Spain), thanks to their project COVID DATA SAVE LIVES [ 34 ]. In [ 35 ], several hypothesis contrasts and the chi-squared and Wilcoxon tests were performed using this dataset. However, model-based statistical techniques and machine learning techniques were uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we analyze the anonymized dataset obtained from the HMhospitals’ network in Madrid (Spain), thanks to their project COVID DATA SAVE LIVES [ 34 ]. In [ 35 ], several hypothesis contrasts and the chi-squared and Wilcoxon tests were performed using this dataset. However, model-based statistical techniques and machine learning techniques were uncovered.…”
Section: Introductionmentioning
confidence: 99%
“…4 5 6 7 8 9 In addition, a number of studies examining HCQ use in the hospitalized setting—particularly use starting within 24-48 hours of admission—have also shown benefit. 19 20 21 22 23 24 That modern, well-conducted non-randomized trials and observational studies would yield results similar to those of RCTs is not surprising as it is the common finding across numerous medical disciplines. 25 26…”
Section: Discussionmentioning
confidence: 95%
“…HCQ then was included in national recommendations in many countries as part of the strategy to fight the pandemic. Table 1 lists the main studies where HCQ was used in the treatment of COVID-19, e.g., retrospective studies of more than 1000 patients and randomized controlled studies [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Whilst most retrospective studies reported clinical improvement with HCQ, randomized controlled studies were stopped because of inefficacy and, eventually, a tendency towards increased overall mortality.…”
Section: Hcq In Covid-19 Diseasementioning
confidence: 99%